RESPON TANAMAN MENTIMUN (Cucumis sativus L.) TERHADAP JENIS POC DAN KONSENTRASI YANG BERBEDA - Andrie KL , Marisi Napitupulu, dan Noor Jannah (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
The research was carried out from May to June 2013, held in the trial station of UNTAG Samarinda.  The Completely Randomised Design was employed for this research with  factorial 3 x 3 and 4 replications.  The first factor was kind of organic fertilzer (P), consisted of 3 sub factors: no organic fertilizer application (p0), using Nasa liquid organic fertilizer (p1), and using Bio Super Active organic fertilizer (p2).  And the second factor was concentration of organic fertilizer (K) that consisted of 3 sub-factors: 2 cc/liter water (k1), 4 cc/liter water (k2), and 6 cc/liter water (k3).Results of the research indicated that kind of Nasa liquid organic fertilizer (p1) and Bio Super Active organic fertilizer (p2) did not affect significantly on crop length, number of crop branch, fruit diameter, fruit length, and fruit weight.  There is a tend that the best fruit weight was attained by applying Bio Super Active organic fertilizer treatment (p2).Different concentration of Nasa and Bio Super Active organic fertilizer affected very significantly fruit weight per 1 fruit, affected significantly on fruit number per crop, but did not affect significantly on crop length, number of crop branch, fruit diameter, and fruit length.  The best fruit weight was attained by applying 4 cc/liter water concentration treatment (k2).Meanwhile, the interaction between kind and different concentration of Nasa and Bio Super Active organic fertilizer did not affect significantly on all parameters observed.